Analisis Faktor-Faktor Yang Dapat Mempengaruhi Tax Avoidance Dengan Kepemilikan Institusional Sebagai Variabel Moderasi - Manurung, Cherryl Berthania Andaristha; Ratnawati, Vince; Nasir, Azwir (Politeknik Ganesha Medan, 2024)
This research aims to find empirical evidence of the influence of firm size, capital intensity and sales growth on Tax Avoidance with Institutional Ownership as a moderating variable. This research was conducted at manufacturing companies registered on the BEI in the 2016-2019 period with a sample size of 77. The sampling technique used the Purposive Sampling Method and the data analysis technique used multiple regression analysis and Moderate Regression Analysis (MRA) via the SPSS application. The research results prove that firm size influences Tax Avoidance, Capital Intensity influences Tax Avoidance, Sales Growth influences Tax Avoidance, Constitutional Ownership influences Tax Avoidance. Institutional Ownership is able to moderate the influence of Capital Intensity and Sales Growth on Tax Avoidance but is not able to moderate the influence of firm size on Tax Avoidance. The implications of this research can be a consideration for companies not to carry out Unacceptable Tax Avoidance which can be detrimental to the country. This is because research results show that companies can carry out Acceptable Tax Avoidance by making better use of several factors such as Capital Intensity and Sales Growth so that there is no need to carry out Tax Avoidance in unacceptable ways that can harm the country. However, company owners must also monitor managers' policies so that they do not do things that are contrary to applicable tax regulations which could have a negative impact on the sustainability of the company.